Finland Education System - Ashok Federick (GoAcademica Research & Publishing, 2020)
If viewed from a geographical perspective, Finland is a Scandinavian country in Northern Europe. A quarter of its territory falls within the Arctic Arctic Ocean Circle. Therefore, the population of this small country must be able to maximize the use of all its psychological and physical potential to maintain and prosper their lives. The country has an area of ​​338,145 km with a population of around 5,518,371 inhabitants and adheres to the socialist (Luthrean-communist) philosophy. Before 1990 Finland relied on the country's income in the agricultural sector, but now Finland is famous as one of the world's technology centers. Finland is able to produce students who are superior compared to students in America in the fields of Science and Mathematics. Like other countries in Europe Finland also adheres to pragmaticism. Religious education is the responsibility of each parent. The Finnish government does not charge tuition fees to its citizens. The core curriculum is handled by tripartite training committees (government, industry and education and training providers). The change of leadership of the state does not change the education policy, so that what was previously programmed by the holders of authority on education policy can continue. The result is that in just 14 years Finland has become the number one education country in the world. In one class there are three teachers (two teachers who focus on delivering the material, one teacher accompanying students who are still lagging behind in the lesson). All teachers must have a master's degree. Undergraduate students are no longer allowed to become teachers even in primary school. Prospective teachers come from the top 10 students on campus who will still be screened more closely. In the evaluation of the Finnish education system there are no Minimum Mastery Criteria (KKM) as in Indonesia, and also no national examination (UAN), but they adhere to policies.